2011
DOI: 10.1111/j.1365-2648.2011.05712.x
|View full text |Cite
|
Sign up to set email alerts
|

An international collaborative study comparing Swedish and Japanese nurses’ reactions to elder abuse

Abstract: Despite cultural differences, responses of Swedish and Japanese nurses were very similar which points to a global 'humanness' of the problem of, and nurses' responses to, elder abuse. Results endorse the value of international collaborations that give information and inspiration to nursing colleagues across cultural boundaries. Results also give hope that global tools for elder abuse assessment and intervention can be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
1
7
0
5
Order By: Relevance
“…[66] Similarly, intuition, suspicions and experience were factors used by public health nurses, nurses, auxiliary nurses, social workers and care workers in the identification of suspected elder abuse cases. [42,46] Recognizing suspected cases of elder abuse can be difficult. [33] The first step in clinical assessment is recognition of a possible abuse situation, followed by the gathering of evidence from a wide range of sources, observation, judgement, decision making and conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[66] Similarly, intuition, suspicions and experience were factors used by public health nurses, nurses, auxiliary nurses, social workers and care workers in the identification of suspected elder abuse cases. [42,46] Recognizing suspected cases of elder abuse can be difficult. [33] The first step in clinical assessment is recognition of a possible abuse situation, followed by the gathering of evidence from a wide range of sources, observation, judgement, decision making and conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Chinese study of 245 student nurses perceptions of elder abuse found that 57.2% of first year students and 38.5% of third year students viewed detection of elder abuse as the responsibility of social workers. [45] A study by Erlingson et al (2012) [46] used a questionnaire based on three hypothetical cases of elder abuse to examine Swedish community-based nurses (n = 81) and Japanese Public Health Nurses (n = 124) experience and responses to abuse. Swedish nurses described an approach that was practical, action-oriented and involved high levels of suspicion and personal intervention to attain increased control over situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a tool can help maintain an index of suspicion for professionals, which is an essential attitude for detecting cases of suspected abuse. Four publications (Erlingsson, Ono, Sasaki, & Saveman, 2012;Sandmoe & Kirkevold, 2013;Sandmoe, Kirkevold, & Ballantyne, 2011;Strümpel & Hackl, 2011) considered the strategies of professionals who are faced with a possible case of abuse and found that knowledge and attitudes can affect the way in which they approach situations of suspected abuse. Strümpel and Hackl (2011) outlined strategies that emerged from interviews with professionals from several European countries on how they addressed domestic violence against older women.…”
Section: The Ability Of Knowledge and Attitudes Of Professionals To Amentioning
confidence: 99%
“…In an international collaborative study comparing Swedish and Japanese nurses’ reaction to elder abuse, similarities in responses to cases were noted despite originating from two different cultures, pointing to the global ‘humanness’ of the problem of elder abuse (Erlingsson et al . ). Nurses, therefore, must be schooled with the knowledge and skills necessary to identify and manage maltreatment among this vulnerable group to rescue and restore dignity, self‐worth and quality of life to the affected individual.…”
Section: Introductionmentioning
confidence: 97%